ANALISIS USAHA TERNAK DOMBA DI DESA TANJUNG JATI KABUPATEN LANGKAT - Deri Ardian,; Media Agus Kurniawan, (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the income of sheep farmers in Tanjung Jati Village, Binjai District, Langkat Regency. It was conducted in Secanggang District, Langkat Regency, North Sumatra Province. The research method used was direct observation, with data collected from both primary and secondary sources. The analysis of sheep farming in Binjai District, Langkat Regency, North Sumatra Province shows that, on average, farmers raise 24.4 sheep, with a profit and loss value of IDR 6,194,783 and a B/C ratio of 1.5. This indicates that sheep farming is economically feasible and worth developing